Social aspirations among adolescents in Mexico - Castillo-Viveros, Nemesio; Zavaleta Betancourt, José Alfredo; Rojas-González, Erika Patricia (Acciones e Investigaciones Sociales, 2021)
The aim of this research article is to analyze the opinions of adolescents that are at risk of falling prey to violence and delinquency in the local municipalities of Xalapa, Poza Rica, Puerto de Veracruz and Coatzacoalcos in the state of Veracruz (Mexico). The field work was carried out in poverty-stricken neighbourhoods as categorized by the Department of Social Development. For the purposes of our research, we took a sampling from primary and secondary schools located within the areas under study, with the participation of 434 adolescents from 10 to 14 years of age. A descriptive approach was adopted to analyze the data, with correlations being discussed and the data analysis carried out using SPSS version 25. It was found that adolescents clearly identify the problems in their family, school, neighbourhood and country. However, they are willing to work for social change. 72% of those surveyed see themselves as a professional in ten years, while 69% see themselves working or studying in ten years’ time. It should be noted that social inequality, social practices, context and culture place limits on their social wellbeing. Therefore, we propose a model of social intervention, implemented by social management, where they are the ones that take decisions concerning their future based on cumulative economic, social, cultural and symbolic capital.